Relationship between job characteristics and music performance anxiety in collaborative pianists working in Slovenian music schools - Babnik, Katarina; Lep, Žan; Habe, Katarina (Frontiers in Psychology, 2025)
IntroductionMusic performance anxiety (MPA) is a significant challenge for amateur and professional musicians, as well as music students. Systematic literature reviews highlight a lack of research on the role of contextual variables in MPA. This study contributes to existing knowledge by examining how job characteristics, particularly job demands and job resources, influence MPA among collaborative pianists.MethodA cross-sectional quantitative study was conducted on 94 collaborative pianists (24% of the population) working at all three levels of the Slovenian music education system. Data were collected through an online survey, including demographic characteristics, objective workload measures, and perceived job characteristics scales (cognitive job demands, emotional demands, job influence, role clarity, role conflict, and organizational justice), along with an adapted MPA scale. Confirmatory factor analysis and internal consistency analysis were conducted for each scale, followed by correlation analysis and a multiple linear regression model to predict MPA.ResultsThe study tested six hypotheses, with mixed support for the proposed relationships. The regression model explained 50% (F = 5.11; df1 = 10, df2 = 51, p < 0.001) of the variance in MPA, with perceived emotional demands (β = 0. 50; t = 3.57; p < 0.001) and role conflict (β = 0.38; t = 2.65; p = 0.011) playing significant roles in predicting MPA.Discussion and conclusionsThe findings enhance the understanding of MPA in the job context and have practical implications for music school management. Future research should explore the interaction between job characteristics and individual psychological resources across diverse professional and cultural contexts with representative samples.